Situasi Genting Pengungsi dan Pekerja Migran di Malaysia yang Berkelanjutan Pasca-Covid-19 - Sheila Devi Michael (Jurnal HAM, 2024)
The COVID-19 pandemic exacerbated the vulnerabilities faced by refugees and migrant workers globally, and Malaysia was no exception, where these groups encountered significant challenges exacerbated by their marginalized legal status. Often perceived as illegal, refugees and migrant workers faced widespread discrimination and neglect during Malaysia's efforts to manage and contain the virus. This environment fostered xenophobic attitudes among both the government and the general population, undermining efforts to protect these vulnerable populations from abuse, exploitation, and discrimination. Compared to international standards, Malaysia's response to safeguarding the rights of refugees and migrant workers fell short, as evidenced by their inadequate protection measures during the pandemic. This paper seeks to shed light on the dire conditions experienced by these groups throughout the COVID-19 crisis and their ongoing precarious situation. Drawing from a range of primary and secondary sources including official statements, mainstream media reports, and findings from local and international organizations, the research underscores persistent challenges faced by refugees and migrant workers. The findings reveal that despite sporadic efforts, the fundamental situation for these vulnerable groups remains largely unchanged, with systemic issues of discrimination and neglect persisting. In response, the paper advocates for urgent reforms and the implementation of comprehensive policies by the Malaysian government to improve conditions and protect the rights of refugees and migrant workers effectively. These reforms are essential not only for meeting international human rights standards but also for fostering a more inclusive and equitable approach to public health crises and broader social welfare policies.